Experimental study on energy performance of a split air-conditioner by using variable thickness evaporative cooling pads coupled to the condenser. (25th July 2016) - Martínez, P.; Ruiz, J.; Cutillas, C.G.; Martínez, P.J.; Kaiser, A.S.; Lucas, M.
Abstract: A well known strategy for improving the performance of air conditioning systems when using air-condensed units is to decrease the ambient inlet airflow temperature by means of an evaporative cooling pad. In this work experiments are conducted in a split air-conditioning system where the condensing unit is modified by coupling different evaporative cooling pads with variable thickness. The impact of the different cooling pads on the overall performance of the air-conditioning system is experimentally determined by measuring the airflow conditions and the energy consumption of the overall air conditioning system, including both the condenser fan and the feedwater recirculation pump of the cooling pads. The aim is to determine the energy efficiency improvement achieved by pre-cooling the ambient airflow compared to a common air-condensed unit and to calculate the optimal pad thickness that maximize the overall COP of the system. Experimental results indicate that the best overall COP is obtained by adding a cooling pad thickness of about 100 mm. At that point the compressor power consumption is reduced by 11.4%, the cooling capacity is increased by 1.8% and finally the overall COP is increased by 10.6%.